Ciclofosfamida en el síndrome nefrótico. - Durán, Sandalio; López, Julio; Aguilar, Juan; Llapur, Juan R.; Cubero, Osiris (Revista Cubana de Pediatría, 2023)
Se realiza un análisis retrospectivo de la experiencia de los autores.